Ta’sîr istî’âb Al-Tarâkib Al-Lughawiyyah Fî Al-Tarjamah Al-‘Arabiyyah Ila Al-Indûnîsiyyah - Ali Maksum; Ubaidillah Ubaidillah (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2022)
The influence of the mastery of Arabic structure on the ability to translate Arabic into Indonesian. The Department of Arabic Language Education prepares its students to become professional Arabic teachers by developing a special curriculum. Among the courses in the curriculum considered as the most important to be mastered by the students are Nahwu courses, because other Arabic language sciences are always related to Nahwu and the number of credits for Nahwu courses is more than other subjects, but many students do not able to translate well. This study aims to determine the effect of the mastery of Arabic structure on seventh semester PBA students on their ability to translate Arabic into Indonesian. In this study, the researcher carried out the following research steps: observations in the PBA department, interviews the head of the department, several students and several PBA lecturers, and distributing the tests to the 7th semester students. The results of the study indicate that students' mastery of the Arabic language structure is quite good with an average value of 6.33 while the ability to translate it is lacking with an average value of 5.1. The correlation between mastery of Arabic structure and ability to translate Arabic into Indonesian is in the medium category with a correlation value of 0.64. After the researchers analyzed the data above, the researcher found that the influence of mastery of Arabic structure on the ability to translate Arabic into Indonesian was 41%, so there were other factors that influenced the ability to translate Arabic into Indonesian which reached 59%.